Answer:
![\textsf{a)}\quad y=8x^2+2x-3](https://img.qammunity.org/2023/formulas/mathematics/college/lf2ro3sdd0rwa40cgf53ifx1wbujsf8slo.png)
![\textsf{b)}\quad y=x^2-2x-4](https://img.qammunity.org/2023/formulas/mathematics/college/akaqdvyfr47iac0jyqhl7qq3wk6syas5z9.png)
Explanation:
Given information:
![x^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/college/j1trlxhw2xynv3ce87y4ap7e1w4fpptmne.png)
![x_1+x_2=-b](https://img.qammunity.org/2023/formulas/mathematics/college/7407t80pt08qpvm8lxn35n9h2q4ej1q4i1.png)
![x_1x_2=c](https://img.qammunity.org/2023/formulas/mathematics/college/n4aspept0aodlk80mors5jkeu932y3kt95.png)
Part (a)
![\textsf{If}\quad x_1=\frac12\quad\textsf{and}\quad x_2=-\frac34](https://img.qammunity.org/2023/formulas/mathematics/college/wcowtmefvhzvq8peo7harc58ard3xy38cf.png)
![\begin{aligned}\implies -b & =\frac12+\left(-\frac34\right)\\ & = \frac24-\frac34\\ & =-\frac14\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/vamk2117liy16q35i93z8c8l1n33ztskk2.png)
![\begin{aligned}\implies c & =\frac12 \cdot \left(-\frac34\right)\\ & = (1 (-3))/(2 \cdot 4)\\ & =-\frac38\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/z9wqxu7lh4uopsw79hooycv29tiy32cq4t.png)
Substituting the found values of b and c into
![x^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/college/j1trlxhw2xynv3ce87y4ap7e1w4fpptmne.png)
![\implies x^2+\frac14x-\frac38=0](https://img.qammunity.org/2023/formulas/mathematics/college/jk3mzg9qjargptv8kvx0xy207z81rqi50b.png)
Multiply both sides by 8 so that coefficients are integers:
![\implies 8x^2+2x-3=0](https://img.qammunity.org/2023/formulas/mathematics/college/moc0af7xuo85pk29uh5hk1hmu9bp2rqgqf.png)
Therefore, the final quadratic equation is:
![y=8x^2+2x-3](https://img.qammunity.org/2023/formulas/mathematics/college/pearutjmt82gfqeaq1uckyqpir9q5avvty.png)
----------------------------------------------------------------------------------------------
Part (b)
![\textsf{If}\quad x_1=1+√(5)\quad\textsf{and}\quad x_2=1-√(5)](https://img.qammunity.org/2023/formulas/mathematics/college/qa8lsezehz06et7yvv6tug8d1xokjqa8q4.png)
![\begin{aligned}\implies -b & =(1+√(5))+(1-√(5))\\ & = 1+1+√(5)-√(5)\\ & =2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/gq1fdpqb3lhxnvfmgvjohkf8sd6jhj4qgm.png)
![\begin{aligned}\implies c & =(1+√(5))(1-√(5))\\ & = 1-√(5)+√(5)-5\\ & =-4\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/1a3qslhoc00ix9dpmxu2tjv93jmhfdil6w.png)
Substituting the found values of b and c into
![x^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/college/j1trlxhw2xynv3ce87y4ap7e1w4fpptmne.png)
![\implies x^2-2x-4=0](https://img.qammunity.org/2023/formulas/mathematics/college/5o5uqzah4x7nkv9przz172x3kfe09abxcu.png)
Therefore, the final quadratic equation is:
![y=x^2-2x-4](https://img.qammunity.org/2023/formulas/mathematics/college/z1cgyy6rocdxuixzawvyoh1ou1389s7ptw.png)